Inside-out vein graft and inside-out artery graft in rat sciatic nerve repair - Barcelos, A. S.; Rodrigues, A. C.; Silva, M. D.; Padovani, C. R. (Wiley-Blackwell, 2003)
Although veins and arteries present similar wall structures, there are differences which may be relevant in peripheral nerve reconstruction. Inside-out vein grafts (IOVG) have been satisfactorily used to repair both motor and sensitive nerves. However, the inside-out artery graft (IOAG) is a new technique and not fully investigated. Our study presents comparative morphological data on nerve regeneration achieved with IOVG and IOAG in the repair of Wistar rat sciatic nerves. Jugular veins and aorta arteries were harvested from donor animals and used inside-out to bridge a 10-mm gap. Animals were sacrificed at 10 weeks to evaluate nerve regeneration. Both techniques presented great variability in nervous tissue, though some animals showed satisfactory results. Different intensities of scarring processes might have interfered with nerve regeneration. Although IOVG and IOAG techniques showed similar morphometric results, in general, IOVG presented a closer-to-normal nerve organization than IOAG.